A 10-year-old child with acute torticollis due to polymicrobial deep neck infection. Issue 1 (6th January 2022) - Guri, Alex; Scheier, Eric
Abstract : Torticollis in children can be a sign of a potentially dangerous disease; the correct diagnosis is not always obvious on history and physical examination. The use of point-of-care ultrasound (POCUS) helps to limit the differential diagnosis and direct appropriate further laboratory and radiology-performed evaluation. We present a case of a 10-year-old child whose deep neck infection (DNI) was timely diagnosed in the paediatric emergency department by early use of POCUS and drained under POCUS guidance after admission to the hospital. The culture from the fluid grew Eikenella corrodens, Streptococcus constellatus and Prevotella buccae . This case demonstrates that DNIs occur in children with acute acquired torticollis, even without fever and demonstrates the importance of early use of POCUS in cases where DNI is a potential diagnosis. Moreover, this case emphasises the importance of microbiological identification of DNIs that can be the key to successful treatment.